UPAYA PEMERINTAH DKI JAKARTA DALAM MELESTARIKAN BUDAYA BETAWI MENURUT PASAL 2 PERATURAN DAERAH DKI JAKARTA NOMOR 4 TAHUN 2015 TENTANG PELESTARIAN KEBUDAYAAN BETAWI - Akhmad Miftahul Achyar (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Akhmad Miftahul Achyar, Lutfi Effendi, Amelia Ayu Paramitha Fakultas Hukum Universitas Brawijaya Jl. MT. Haryono No. 169 Malang Email : akhmadmiftahul17@gmail.com ABSTRAK Permasalahan yang terdapat dalam penelitian ini adalah adanya suatu permasalahan pelaksanaan Peraturan Daerah DKI Jakarta Nomor 4 Tahun 2015. Di dalam pasal 2 ini memuat tujuan apa yang akan dilaksanakan oleh Pemerintah DKI Jakarta. Tetapi Peraturan penyelenggara untuk melaksanakan kegiatan pelestarian kebudayaan Betawi hanya terdapat 3 peraturan. Urgensi penelitian ini adalah untuk memberikan kepastian hukum terkait Pelestarian kebudayaan Betawi. Berdasarkan penelitian ini disimpulkan bahwa dalam hambatan pemerintah DKI Jakarta dalam menjalankan peraturan daerah DKI Jakarta nomor 4 tahun 2015 yaitu, kurangnya peraturan pelaksana, kurangnya koordinasi, sosialisasi, kurangnya kesadaran masyarakat dan pejabat dinas akan melestarikan kebudayaan Betawi. Berdasarkan hasil penelitian yang telah dilakukan oleh penulis, berhubungan dengan upaya pemerintah DKI Jakarta dalam menjalankan Peraturan Daerah DKI Jakarta nomor 4 tahun 2015, Pemerintah daerah DKI Jakarta akan terus membuat regulasi-regulasi baru yang mengatur hal-hal teknis dalam implementasi Peraturan Daerah DKI Jakarta nomor 4 tahun 2015, serta meningkatkan koordinasi Peraturan Daerah DKI Jakarta tentang pelestarian kebudayaan Betawi dan Peraturan Gubernur DKI Jakarta tentang teknis implementasinya kepada semua stakeholder, lembaga / organisasi kebudayaan, dan masyarakat Jakarta melalui sosialisasi berjenjang, serta penyediaan ruang bagi para pelaku seni. Meningkatkan kolaborasi antar berbagai elemen baik dari pemerintah, stakeholder, organisasi kebudayaan, dan masyarakat Jakarta dalam pelaksanaan pengawasan pelestarian kebudayaan Betawi, serta melakukan inovasi baru untuk menunjang pelestarian kebudayaan Betawi. Kata Kunci: Peraturan Daerah DKI Jakarta nomor 4 tahun 2015, Peraturan Pelaksana, Pelestarian Kebudayaan Betawi Abstract The issue contained in this study is the existing problem in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015. In Article 2 covers the aims concerning the implementation regulation conducted by Government of DKI Jakarta. However, the delegated legislations on the implementation of Betawi cultural preservation activities only consists of 3 regulations. The urgency of this research is to provide legal certainty related to the preservation of Betawi culture. Based on this research, it was concluded that there are some obstacles faced by Government of DKI Jakarta in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015, namely: lack of implementing regulations, lack of coordination, socialization, lack of public awareness and limited government officials that will preserve Betawi culture. Based on the results of research conducted by the authors, in connection with the efforts of Government of DKI Jakarta in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015, the Regional Government of DKI Jakarta will continue to issue new regulations governing technical matters in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015, as well as improving coordination between Regional Regulation of DKI Jakarta on the preservation of Betawi culture and the Governor Regulation of DKI Jakarta on the technical implementation to all stakeholders, institutions / cultural organizations, and the people of Jakarta through tiered socialization, as well as the provision on providing space for art actors. Improving collaboration between various elements from the government, stakeholders, cultural organizations, and the people of Jakarta in the implementation of supervision of betawi cultural preservation, as well as making new innovations to support the preservation of Betawi culture.Abstract The issue contained in this study is the existing problem in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015. In Article 2 covers the aims concerning the implementation regulation conducted by Government of DKI Jakarta. However, the delegated legislations on the implementation of Betawi cultural preservation activities only consists of 3 regulations. The urgency of this research is to provide legal certainty related to the preservation of Betawi culture. Based on this research, it was concluded that there are some obstacles faced by Government of DKI Jakarta in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015, namely: lack of implementing regulations, lack of coordination, socialization, lack of public awareness and limited government officials that will preserve Betawi culture. Based on the results of research conducted by the authors, in connection with the efforts of Government of DKI Jakarta in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015, the Regional Government of DKI Jakarta will continue to issue new regulations governing technical matters in the implementation of Regional Regulation of DKI Jakarta Number 4 of 2015, as well as improving coordination between Regional Regulation of DKI Jakarta on the preservation of Betawi culture and the Governor Regulation of DKI Jakarta on the technical implementation to all stakeholders, institutions / cultural organizations, and the people of Jakarta through tiered socialization, as well as the provision on providing space for art actors. Improving collaboration between various elements from the government, stakeholders, cultural organizations, and the people of Jakarta in the implementation of supervision of betawi cultural preservation, as well as making new innovations to support the preservation of Betawi culture.